Absence of Telomerase Activity in Malignant Bone Tumors and Soft-Tissue Sarcomas. (2002) - Lauer, Nina K.; Maier, Sandra M.; Oberringer, Martin; Schulte, Michael; Mutschler, Wolf; Hanselmann, Rainer G.; Schartl, Manfred; Scherer, Stefan J.; Wirbel, Reiner J.
Abstract : Purpose: Telomerase activity appears to play a crucial role in the development of many tumors. More than 80% of all malignant human tumors show an increased telomerase activity. However, conflicting results have been reported about telomerase activity in sarcomas. The aim of the study was to obtain more information about telomerase activity in sarcomas based on a large number of cases. Methods: Telomerase activity was measured in 69 different tumor samples (33 malignant bone tumors and 36 soft tissue sarcomas). Tumor samples were obtained intraoperatively and frozen immediately in liquid nitrogen. Telomerase activity was detected by the telomeric repeat amplification assay (TRAP-assay). Results: Only 7% of the samples showed telomerase activity. No correlation between staging and telomerase activity could be observed. Discussion: The fact that only five out of 69 examined tumor samples showed a telomerase activity provides experimental evidence that in sarcomas the reactivation of telomerase may play a subordinate role. Our results suggest that alternative mechanisms for cell immortalization, yet to be determined, seem to be involved in the development and/or maintenance of soft-tissue sarcomas and malignant bone tumors.